2016
DOI: 10.1007/s00018-016-2164-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical perspectives of TRAIL: insights into central nervous system disorders

Abstract: The TNF-related apoptosis inducing ligand TRAIL is a member of the TNF superfamily that has been firstly studied and evaluated for its anti-cancer activity, and the insights into its biology have already led to the identification of several TRAIL-based anticancer strategies with strong clinical therapeutic potentials. Nonetheless, the TRAIL system is far more complex and it can lead to a wider range of biological effects other than the ability of inducing apoptosis in cancer cells. By virtue of the different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 121 publications
1
31
0
5
Order By: Relevance
“…During the last two decades, several groups have addressed the role of TRAIL not only in cancer but also in other non-neoplastic diseases. Along with other Authors, we have found an inverse correlation between circulating TRAIL and the presence or the adverse prognosis of different pathological conditions including cardiovascular disease (CVD), type 1 and type 2 diabetes, and neurological disorders [11][12][13][14][15][16][17][18][19][20][21]. In addition, our results have provided insights into the therapeutic potential of recombinant TRAIL administration [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 82%
“…During the last two decades, several groups have addressed the role of TRAIL not only in cancer but also in other non-neoplastic diseases. Along with other Authors, we have found an inverse correlation between circulating TRAIL and the presence or the adverse prognosis of different pathological conditions including cardiovascular disease (CVD), type 1 and type 2 diabetes, and neurological disorders [11][12][13][14][15][16][17][18][19][20][21]. In addition, our results have provided insights into the therapeutic potential of recombinant TRAIL administration [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 82%
“…To test this further, we measured the protein levels of the inflammatory cytokines, IL-6, previously shown to be increased in patients and animal models across several MPS disorders [23][24][25]. We have also measured the levels of TNFSF10 (TRAIL), which has been associated with neuroinflammation in adult neurodegenerative diseases including Alzheimer's disease and multiple sclerosis [26,27]. We found that in the majority of MPS samples, levels of IL-6 and TRAIL proteins showed a trend for an increase.…”
Section: Microastroglyosis and Neuroinflammationmentioning
confidence: 99%
“…The article of B. Toffoli et al addresses the role of two other cytokines belonging to the TNF family. Osteoprotegerin (OPG) and TNF-related apoptosis-inducing ligand (TRAIL) are two factors showing controversial effects on several physiopathological contexts [7, 8]. In a preclinical model, the authors show that dyslipidaemia and diabetes, two risk factors for cardiovascular disease, modify the vascular and cardiac expression of OPG and TRAIL leading to an increased OPG/TRAIL ratio.…”
mentioning
confidence: 99%